Politeness Pragmatemes in the Elementary Level French Textbook Edito A1 - Sidorovič, Elina (Verbum, 2024)
Politeness pragmatemes, such as greetings, thanks, and apologies, are common expressions used to convey politeness in everyday communication. Although native speakers do not always pay attention to these expressions, they are unique due to their strictly limited "ritual" use. This article analyzes the politeness pragmatemes present in the Edito A1 textbook by Didier Editions (2016), intended for beginner learners of French as a foreign language. The chosen textbook integrates these expressions into various contexts, such as greetings, introductions, orders, and telephone conversations, etc. The article also describes the syntactic and morphological characteristics of politeness pragmatemes, showing that they can come from any part of speech (noun, adjective, participle, verb, adverb, interjection). Finally, the analysis shows that the inclusion of these pragmatemes in the textbook aims to familiarize learners with social interactions in French and to promote mutual respect through communication.